Stepanov-Like Asymptotical Almost Periodic Functions and an Application. (4th December 2018) - Li, Yongkun; Wang, Yaolu; Xiang, Jianglian
Abstract : In this paper, we first study some basic properties of Stepanov-like asymptotical almost periodic functions including the completeness of the space of Stepanov-like asymptotical almost periodic functions. Then, as an application, based on these and the contraction mapping principle, we obtain sufficient conditions for the existence and uniqueness of Stepanov-like asymptotical almost periodic solutions for a class of semilinear delay differential equations.